Murder at the Merton library [large type] - Penrose, Andrea (Penrose, Andrea. Wrexford & Sloane historical mystery, 2023)
"Responding to an urgent plea from a troubled family friend, the Earl of Wrexford journeys to Oxford only to find the reclusive university librarian has been murdered and a rare manuscript has gone missing. The only clue is that someone overheard an argument in which Wrexford's name was mentioned. At the same time, Charlotte -- working under her pen name, A. J. Quill -- must determine whether a laboratory fire was arson and if it's connected to the race between competing consortiums to build a new type of ship -- one that can cross the ocean powered by steam rather than sails -- with the potential to revolutionize military power and world commerce. That the race involves new innovations in finance and entrepreneurship only adds to the high stakes -- especially as their good friend Kit Sheffield may be an investor in one of the competitors. As they delve deeper into the baffling clues, Wrexford and Charlotte begin to realize that things are not what they seem. An evil conspiracy is lurking in the shadows and threatens all they hold dear -- unless they can tie the loose threads together before it's too late . . ."--